Clinical Characteristics and Self-Harm in Forensic Psychiatric Patients - Laporte, Natalie; Ozolins, Andrejs; Westling, Sofie; Westrin, Åsa; Wallinius, Märta (Frontiers in Psychiatry, 2021)
Self-harm, comprising non-suicidal self-injury, and suicide attempts, is a serious and potentially life-threatening behavior that has been associated with poor life quality and an increased risk of suicide. In forensic populations, increased rates of self-harm have been reported, and suicide is one of the leading causes of death. Aside from associations between self-harm and mental disorders, knowledge on self-harm in forensic psychiatric populations is limited. The purpose of this study was to characterize the clinical needs of a cohort of forensic psychiatric patients, including self-harm and possible risk factors thereof. Participants (N = 98) were consecutively recruited from a cohort of forensic psychiatric patients in Sweden from 2016 to 2020. Data were collected through file information, self-reports, and complemented with semi-structured interviews. Results showed that self-harm was common among the participants, more than half (68.4%) of whom had at some point engaged in self-harm. The most common methods of non-suicidal self-injury were banging one's head or fist against a wall or other solid surface and cutting, and the most common method of suicide attempt was hanging. The most prominent functions of non-suicidal self-injury among the participants were intrapersonal functions such as affect regulation, self-punishment, and marking distress. Self-harm in general was associated to neurodevelopmental disorders (p = 0.014, CI = 1.23–8.02, OR = 3.14) and disruptive impulse-control and conduct disorders (p = 0.012, CI = 1.19–74.6, OR = 9.41), with reservation to very wide confidence intervals. Conclusions drawn from this study are that self-harm was highly prevalent in this sample and seems to have similar function in this group of individuals as in other studied clinical and non-clinical groups.